Land forest area in Peninsular Malaysia from 1996-2000 - Nik Hashim, Nik Hazlan (2002)
The tropical rain forest is one of the most complex ecosystems in the world. The forests are of vital economic and ecological importance to the country. Apart from its socio-economic role, the forests also play an important protective function such as the maintenance of environmental stability, minimization of damage to rivers and agriculture land by floods and erosion and the safeguarding of water supplies. The forest area in Peninsular Malaysia has decreased from 1990 - 1998. The reason would be because of rapid development in Malaysia during that period. To maintain source and forest area, present forest management should be maintain and upgraded. This is not only to assure long term wood supply but also to preserve stability of environment and wildlife. Understanding this situation, forest in Peninsular Malaysia had been organized using perfect method so that wood production would be continuously, preservati9n and protection of multiple wildlife, stability of climate and ecological stability for production of forest for continuously purpose.